Asymptotics of Solutions of Nonautonomous Second-Order Ordinary Differential Equations Asymptotically Close to Linear Equations - Evtukhov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Asymptotic representations are obtained for a broad class of monotone solutions of nonautonomous binary differentialequations of the second order that are close in a certain sense to linear equations.